2006
DOI: 10.1029/2005gc001223
|View full text |Cite
|
Sign up to set email alerts
|

Glacial/interglacial changes in southern Africa: Compound‐specific δ13C land plant biomarker and pollen records from southeast Atlantic continental margin sediments

Abstract: [1] This is part 2 of a study examining southwest African continental margin sediments from nine sites on a north-south transect from the Congo Fan (4°S) to the Cape Basin (30°S) representing two glacial (MIS 2 and 6a) and two interglacial stages (MIS 1 and 5e). Contents, distribution patterns, and molecular stable carbon isotope signatures of long-chain n-alkanes (C 27 -C 33 ) and n-alkanols (C 22 -C 32 ) as indicators of land plant vegetation of different biosynthetic types were correlated with concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 62 publications
5
41
1
2
Order By: Relevance
“…The sharp excursion in core SL6 δ 13 C wax signal to more negative values suggests a large increase in C 3 plant input into the sediments during this same period, inferring a change to more temperate C 3 grasses during the LGM and late glaciation. Consistent with this, Dupont et al (2011), Rommerskirchen et al (2006, and Scott (2002) concluded that there is very little evidence for increased C 4 grasses during the LGM in sub-tropical Southern Africa, and that C 3 grasses more than likely dominated the region during this period. This is in direct contrast to records studied in the tropical regions of Africa where there is strong evidence for C 4 plant expansion during the LGM (Castañeda et al, 2009;Sinninghe Damsté et al, 2011).…”
Section: The Last Glacial Maximum and Deglacialsupporting
confidence: 61%
See 2 more Smart Citations
“…The sharp excursion in core SL6 δ 13 C wax signal to more negative values suggests a large increase in C 3 plant input into the sediments during this same period, inferring a change to more temperate C 3 grasses during the LGM and late glaciation. Consistent with this, Dupont et al (2011), Rommerskirchen et al (2006, and Scott (2002) concluded that there is very little evidence for increased C 4 grasses during the LGM in sub-tropical Southern Africa, and that C 3 grasses more than likely dominated the region during this period. This is in direct contrast to records studied in the tropical regions of Africa where there is strong evidence for C 4 plant expansion during the LGM (Castañeda et al, 2009;Sinninghe Damsté et al, 2011).…”
Section: The Last Glacial Maximum and Deglacialsupporting
confidence: 61%
“…3) recorded both 6 ± 2 °C cooler LGM temperatures and c. 50% less precipitation than the Holocene (Truc et al, 2013) during the LGM. These cooler and drier glacial conditions could arguably have been the cause for a shift to C 3 grass dominance in the Mfabeni, which tend to have an advantage over C 4 grasses at lower temperatures (Kotze and O' Conner, 2000;Sage et al, 1999), and appear to have dominated the sub-tropical and WRZ of Southern Africa during the LGM (Dupont et al, 2011;Rommerskirchen et al, 2006;Scott, 2002). These conditions persist with %TOC fluctuating at below average core levels, the δ 13 C bulk signal becoming increasingly more negative and dry grassland palynology signature continuing until c. 15 kcal yr BP.…”
Section: Palaeoclimate Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, δ 13 C of plant biomarkers in sediment cores off the East Atlantic coast close to the river mouths of the Congo and Angola basins indicate 3-4 higher values during glacial times 41 , similar to evidence from the Guinea Plateau margin recording Sahara/Sahel vegetation 42 . A comparable marine geological study from the Cariaco Basin in the tropical West Atlantic reported a 4-5 δ 13 C decrease in leaf waxes from the Last Glacial Maximum (LGM) to the preboreal Holocene 43 .…”
Section: Climate and Co 2 -Induced Changes In Wetland Ecosystemsmentioning
confidence: 73%
“…Long-chain n-alkanes (≥C27), n-FAs (≥C22) and n-alkanols (≥C22) are generally considered to predominantly derive from vascular plant waxes, which are also regarded as tracers of terrestrial vascular plant OM [26][27][28][29]. Figures 3b, 4b and 5b illustrate that more plant wax was detected in the cold season (December, February-March).…”
Section: Insight From Lipid Biomarker Composition Plant Wax Lipidsmentioning
confidence: 99%